A critical appraisal of the methodology and quality of evidence of systematic reviews and meta-analyses of traditional Chinese medical nursing interventions: a systematic review of reviews. Issue 11 (14th November 2016) - Jin, Ying-Hui; Wang, Guo-Hao; Sun, Yi-Rong; Li, Qi; Zhao, Chen; Li, Ge; Si, Jin-Hua; Li, Yan; Lu, Cui; Shang, Hong-Cai
Abstract : Objective: To assess the methodology and quality of evidence of systematic reviews and meta-analyses of traditional Chinese medical nursing (TCMN) interventions in Chinese journals. These interventions include acupressure, massage, Tai Chi, Qi Gong, electroacupuncture and use of Chinese herbal medicines—for example, in enemas, foot massage and compressing the umbilicus. Design: A systematic literature search for systematic reviews and meta-analyses of TCMN interventions was performed. Review characteristics were extracted. The methodological quality and the quality of the evidence were evaluated using the Assessment of Multiple Systematic Reviews (AMSTAR) and Grading of Recommendations Assessment, Development and Evaluation (GRADE) approaches. Result: We included 20 systematic reviews and meta-analyses, and a total of 11 TCMN interventions were assessed in the 20 reviews. The compliance with AMSTAR checklist items ranged from 4.5 to 8 and systematic reviews/meta-analyses were, on average, of medium methodological quality. The quality of the evidence we assessed ranged from very low to moderate; no high-quality evidence was found. The top two causes for downrating confidence in effect estimates among the 31 bodies of evidence assessed were the risk of bias and inconsistency. Conclusions: There is room for improvement in the methodological quality of systematic reviews/meta-analyses of TCMN interventions published in Chinese journals. Greater efforts should be devoted to ensuring a more comprehensive search strategy, clearer specification of the interventions of interest in the eligibility criteria and identification of meaningful outcomes for clinicians and patients (consumers). The overall quality of evidence among reviews remains suboptimal, which raise concerns about their roles in influencing clinical practice. Thus, the conclusions in reviews we assessed must be treated with caution and their roles in influencing clinical practice should be limited. A critical appraisal of systematic reviews/meta-analyses of TCMN interventions is particularly important to provide sound guidance for TCMN.